The macroeconomic factors affecting housing demand in Malaysia - Sebri, Kamarul Hisyam (2022)
In 2020, the surplus of houses and serviced apartments reached a record high of 53,171 units, according to the recent NAPIC statistics. Meanwhile, housing transaction volume decreased on average by 20.6% between 2011 and 2015 and 2016 and 2020. This illustrates a pattern whereby there are more supplies than demands.The objectives of this study is to identify the government policies and measures to minimizing housing overhang and measure the relationship between macroeconomic variables and the housing demand. The first objective finds that government policies and initiatives in minimising property overhang can be categorised into financing policies, levy and taxation exemption, affordable housing policies and government housing finance assistance programme. From the second objective, it was identified the trend in the Malaysian housing demand is related to changes in the gross domestic product (GDP), population, inflation rate, house price index (HPI), interest rate and consumer price index (CPI). The housing transaction data (representing the demand) were collected from Valuation and Property Services Department of the Ministry of Finance Malaysia from 1990 to 2020. Third objective achieved by MRA shows that three macroeconomics factors, gross domestic product (GDP), population and interest rate are significantly influencing housing demand from 1990 to 2020. The research results indicates that increasing GDP is necessary to increase housing demand in Malaysia, that interest rates must be carefully managed to match the current economic environment, and that population growth is crucial to a developing economy. According to these findings, the study strongly advises the government that more SME and FDI should be attracted to the country in order to increase job opportunities and disposable income for the populace. By regulating interest rates, BNM is a significant factor in preserving the housing market. In order to reduce the housing overhang, the government has also implemented a number of strategies and policies but to no avail. The finding is useful for speculators, investors, and buyers to understand which factors to consider when making a housing investment decision and serve as a guide for the government in stabilizing Malaysia's housing market.